2023
DOI: 10.1039/d3cp03844k
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of superconductivity in metallic boron–carbon compounds from 0 to 100 GPa by high-throughput screening

Feng Zheng,
Yang Sun,
Renhai Wang
et al.

Abstract: Boron carbon compounds have been shown to have feasible superconductivity. In our earlier paper [Zheng et al., Phys. Rev. B 107, 014508 (2023)], we identified a new conventional superconductor of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Before the final T c calculations, we apply the E filter to identify structures with strong EPC strength based on the fast frozen-phonon calculations of zone-center EPC strength . This method is particularly efficient in identifying phonon-mediated superconductors in the borides and hydrides, where the zone-center phonon modes contributed significantly to the EPC. ,,, By setting a threshold of 0.1 for the zone-center EPC strength (λ Γ > 0.1), we ultimately identified 23 materials for further superconductivity calculations. The zone-center EPC contributions are shown in Figures S1–S11.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the final T c calculations, we apply the E filter to identify structures with strong EPC strength based on the fast frozen-phonon calculations of zone-center EPC strength . This method is particularly efficient in identifying phonon-mediated superconductors in the borides and hydrides, where the zone-center phonon modes contributed significantly to the EPC. ,,, By setting a threshold of 0.1 for the zone-center EPC strength (λ Γ > 0.1), we ultimately identified 23 materials for further superconductivity calculations. The zone-center EPC contributions are shown in Figures S1–S11.…”
Section: Resultsmentioning
confidence: 99%
“…Many attempts have been made to identify new superconducting phases derived from the MgB 2 compound, such as chemical doping or substitution, resulting in compounds like Mg 1– x Li x B 2 and Mg 1– x Zr x B 2 , and MgB 2 -like boride systems such as MoB 2 and WB 2 . Recently, we have shown that the Brillouin zone-centered EPC strength can be a simple descriptor to identify phonon-mediated superconducting materials in hydrides and borides. This greatly reduced the computational cost in the high-throughput screening of boride superconductors. While we identified a few novel boride systems that exhibit an interesting high T c , their thermodynamic stabilities are not sufficiently high for synthesis, and the structural motifs are still very close to MgB 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this approach has been widely used to rapidly screen possible high- T c superconductors, such as Li 3 ZrB 8 , Ca 3 YB 8 , and MB 3 C (M = Li, Ca, Sr, Ti and V). 63–65 Fig. 2b illustrates the summation of zone-center EPC of all modes, , of these metastable Mg–La–B structures.…”
Section: Resultsmentioning
confidence: 99%